Mapping Modernisms: Art, Indigeneity, Colonialism - Harney, Elizabeth; Phillips, Ruth B. (Ruth Bliss) (Objects/histories : critical perspectives on art, material culture, and representation, 2018)
Mapping Modernisms" brings together scholars working around the world to address the modern arts produced by indigenous and colonized artists. Expanding the contours of modernity and its visual products, the contributors illustrate how these artists engaged with ideas of Primitivism through visual forms and philosophical ideas. Although often overlooked in the literature on global modernisms, artists, artworks, and art patrons moved within and across national and imperial borders, carrying, appropriating, or translating objects, images, and ideas. These itineraries made up the dense networks of modern life, contributing to the crafting of modern subjectivities and of local, transnationally-inflected modernisms. Addressing the silence on indigeneity in established narratives of modernism, the contributors decenter art history's traditional Western orientation and prompt a re-evaluation of canonical understandings of twentieth-century art history. 'Mapping Modernisms' is the first book in Modernist Exchanges, a multivolume project dedicated to rewriting the history of modernism and modernist art to include artists, theorists, art forms, and movements from around the world."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Amérique du Nord: arts premiers - Berlo, Janet Catherine; Phillips, Ruth B. (Terre indienne, 2006)
Replaçant chaque oeuvre dans son contexte familial, social, géographique, économique et spirituel, cet album présente l'art des peuples premiers d'Amérique du Nord, des Inuits aux peuples des déserts du sud-ouest des Etats-Unis, des origines à la période contemporaine
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé